Thinking about Video Games : Interviews with the Experts - Heineman, David S. (Book collections on Project MUSE., 2015)
The growth in popularity and complexity of video games has spurred new interest in how games are developed and in the research and technology behind them. David Heineman brings together some of the most iconic, influential, and interesting voices from across the gaming industry and asks them to weigh in on the past, present, and future of video games--Publisher's description.